Doing Bodies in YouTube Videos about Contested Illnesses. (December 2022) - Groenevelt, Irene; Haan, Sanneke de; Slatman, Jenny
This article is based on an online ethnographic study of Dutch women who use YouTube as a medium to document their contested illness experiences. During 13 months of observations between 2017 and 2019, we followed a sample of 16 YouTubers, and conducted an in-depth analysis of 30 YouTube videos and of 7 interviews. By adopting a 'praxiographic' approach to social media, and by utilising insights from phenomenological theory, this study teases out how bodies are 'done' in (the making of) these YouTube videos. We describe three types of bodies: (1) inert bodies, (2) experienced bodies, and (3) authentic bodies. Ultimately, this study shows how vlogging about contested illness is a practice in which bodies are continually (re)configured, and through which the 'invisibility' of a sufferer's condition can obtain social visibility.